Neonatal seizures alter NMDA glutamate receptor GluN2A and 3A subunit expression and function in hippocampal CA1 neurons - Zhou, Chengwen; Sun, Hongyu; Klein, Peter M.; Jensen, Frances E. (Frontiers in Cellular Neuroscience, 2015)
Neonatal seizures are commonly caused by hypoxic and/or ischemic injury during birth and can lead to long-term epilepsy and cognitive deficits. In a rodent hypoxic seizure (HS) model, we have previously demonstrated a critical role for seizure-induced enhancement of the AMPA subtype of glutamate receptor (GluA) in epileptogenesis and cognitive consequences, in part due to GluA maturational upregulation of expression. Similarly, as the expression and function of the NMDA subtype of glutamate receptor (GluN) is also developmentally controlled, we examined how early life seizures during the critical period of synaptogenesis could modify GluN development and function. In a postnatal day (P)10 rat model of neonatal seizures, we found that seizures could alter GluN2/3 subunit composition of GluNs and physiological function of synaptic GluNs. In hippocampal slices removed from rats within 48-96 hours following seizures, the amplitudes of synaptic GluN-mediated evoked excitatory postsynaptic currents (eEPSCs) were elevated in CA1 pyramidal neurons. Moreover, GluN eEPSCs showed a decreased sensitivity to GluN2B selective antagonists and decreased Mg2+ sensitivity at negative holding potentials, indicating a higher proportion of GluN2A and GluN3A subunit function, respectively. These physiological findings were accompanied by a concurrent increase in GluN2A phosphorylation and GluN3A protein. These results suggest that altered GluN function and expression could potentially contribute to future epileptogenesis following neonatal seizures, and may represent potential therapeutic targets for the blockade of future epileptogenesis in the developing brain.